Equality and Complementarity in the Qur'an: A Thematic Exegesis of Gender Relations - Mukhlis Widodo; Aceng Zakaria (QiST: Journal of Quran and Tafseer Studies, 2026)
Contemporary discussions on gender in the Qur'an have generated extensive scholarly debate, particularly regarding equality, authority, social roles, and justice. Although previous studies have made important contributions, much of the existing scholarship remains fragmented, often focusing on isolated controversial verses or approaching the issue primarily through legal, ideological, or apologetic frameworks. Consequently, there remains a significant gap in studies that reconstruct the Qur'an's discourse on gender through an integrated thematic exegetical perspective that connects theological, ethical, historical, and social dimensions. This study addresses that gap by employing a qualitative library research design using the thematic exegetical (tafsīr mawḍū‘ī) method. It analyzes selected Qur'anic verses related to human creation, spiritual accountability, reciprocity, family structure, inheritance, and social responsibility, while engaging both classical tafsir and contemporary scholarship on gender in Islam. The findings show that the Qur'an upholds the ontological and spiritual equality of men and women while also recognizing certain contextual and functional distinctions in social and familial responsibilities. These distinctions, however, are not framed as a theological basis for absolute hierarchy, but rather as part of a justice-oriented moral order grounded in reciprocity, accountability, and shared human dignity. The significance of this study lies in its contribution to contemporary global debates on religion, gender, and scriptural interpretation by offering a balanced Qur'anic framework that may inform discussions on gender justice, Islamic education, ethical family relations, and inclusive religious discourse in both Muslim and plural societies.